Integrated Curriculum Reform and its Impact on Science Education: Why is the West Falling behind East Asia in PISA and TIMSS? - Qianruo Shen (Nonpartisan Education Review)
This paper investigates why western nations underperform in PISA and TIMSS compared to East Asia and explores the root causes of the decline in science education. By analyzing TIMSS data and comparing the science curricula and teacher qualifications in North America and East Asia, the article reveals how the integrated curriculum reform, promoted by UNESCO, has led to a severe and protracted declination, particularly in physics and chemistry. The excessive amount of non-basic contents and the interdisciplinary approach, of the integrated curricula, have diluted the focus on physics and chemistry, which are the foundation stone of science. Moreover, science teachers with general science degree other than subject-specific credentials lack knowledge in physical science, leaving students with poor mastery of the fundamental knowledge and skills; and underprepared for advanced scientific study and STEM careers. Consequently the U.S. and some other western nations are facing a crisis in cultivation of STEM talents and qualified labor force. It is critical for the West to take bold steps immediately and rebuild the foundation of their science education. Some suggestions are provided.